2021
DOI: 10.1186/s40337-021-00379-8
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming limitations of self-report: an assessment of fear of weight gain in anorexia nervosa and healthy controls using implicit association tests

Abstract: Background Fear of weight gain is a characteristic feature of anorexia nervosa (AN), and reducing this fear is often a main target of treatment. However, research shows that 20% of individuals with AN do not report fear of weight gain. Studies are needed that evaluate the centrality of fear of weight gain for AN with a method less susceptible to deception than self-report. Methods We approximated implicit fear of weight gain by measuring implicit d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 51 publications
(45 reference statements)
0
2
0
Order By: Relevance
“…In recent years, intensive research has resulted with regard to the significance of weight gain anxiety for the onset and maintenance of eating disorders [24,25]. The aim of this study was to indicate the components of anxiety as measured by the BMAS-20 scale and to compare the characteristics of the two constructs in order to better understand their origins and the functions they play.…”
Section: Study 3-characteristics Of Anxiety Related To Weight Changementioning
confidence: 99%
“…In recent years, intensive research has resulted with regard to the significance of weight gain anxiety for the onset and maintenance of eating disorders [24,25]. The aim of this study was to indicate the components of anxiety as measured by the BMAS-20 scale and to compare the characteristics of the two constructs in order to better understand their origins and the functions they play.…”
Section: Study 3-characteristics Of Anxiety Related To Weight Changementioning
confidence: 99%
“…Interestingly, in some studies the fear of losing self-control has been found to be the most important predictor of eating disorders [21,22]. Previous studies showing a positive relationship between weight gain anxiety and psychopathological behaviors have focused mainly on bulimia nervosa and anorexia nervosa [23,24]. Styk et al [20] have drawn attention to yet another aspect related to the anxiety experienced by patients with eating disorders, which is the anxiety about losing weight.…”
Section: Introductionmentioning
confidence: 99%